Photocatalytic performance of novel chromium oxide-silicon dioxide decorated on multi-walled carbon nanotubes and graphene oxide nanocomposites: Preparation, structural, and optimization - Ashraf, Muhammad Aqeel; Liu, Zhenling; Zheng, Dongfang; Li, Cheng; Peng, Wan Xi; Fakhri, Ali (Elsevier, 2020)
In this project, we successfully prepared Cr2O3-SiO2/graphene oxide (GO) or multi-walled carbon nanotubes (MWCNTs) by microwave/ultrasonic/hydrothermally method, aiming for the photo-degradation capture of Parathion compound from aqueous solutions. For the removal of Parathion, the photocatalysis properties is different and the apparent degradation amount sequence is SiO2 < Cr2O3-SiO2 < Cr2O3-SiO2/MWCNTs < Cr2O3-SiO2/GO nano-catalyst. Compared with bare SiO2 particles, Cr2O3-SiO2, and Cr2O3-SiO2/MWCNTs, the prepared Cr2O3-SiO2/GO exhibits the excellent photocatalytic performance for the UV light degradation of Parathion compound. The maximum photo-degradation of Parathion by Cr2O3-SiO2/GO was carried out after 60 min of contact time under UV light. The response surface method with box-behnken design was used to optimization of Parathion photo-degradation. Moreover, the good stability and convenient recycling of the prepared Cr2O3-SiO2/MWCNTs and Cr2O3-SiO2/GO nanocomposites further make it have excellent application aim in removal of organic pollution. © 2019 Elsevier B.V.